Analysis of results for test 1, test 2 and final exam MTH3004 for May 2003/2004 - Md Ariffin, Latifah; Kilicman, Adem; Zainuddin, Hishamuddin (2005)
The Department Of Mathematics, Faculty of Science at Universiti Putra Malaysia (UPM) offers several basic Mathematics Courses for undergraduate students from other departments and faculties in UPM. These courses are Introduction to Algebra (MTH3001), Introduction to Calculus (MTH3002), Statistics for Applied Science (MTH3003), and Introduction to Applied Mathematics for Business and Economics(MTH3004). As a record, these four courses are essentials for students from other departments and faculties in UPM. We select MTH3004 as our sample. MTH3004 offers a selection of basic topics from calculus and algebra including its applications in business and economics. This study is conducted to identify difficulties student’s faces the most in learning this mathematics course. In this study we identify the difficult topics based on analysis of results for test 1, test 2 and final exam in May semester year 2003/2004. The analysis that we conducted are done manually. We calculate the correct answers and wrong answers in percentages for each questions asked in these assessments. Then, based on the percentages, bar graphs are drawn in Microsoft Excel worksheets. From these bar graphs, we can have a better view on questions which has the highest quantity of students who gave the wrong answers. Therefore, we could identify topics that are the most challenging and less challenging in MTH3004. Apart from our general objectives as stated briefly in the abstract above, our specific objective mainly are to identify the most difficult topics in MTH3004 based on student’s performances in assessments which are conducted as evaluations of the course. Numbers of respondents are small in Test 2 compared to Test 1 and Final Exam. This is because we manage to collect data from only one group as for the other groups the data are unavailable. It is due to the reason that on Test 2, each group’s test was handled individually by the course instructor respectively. From this study, we will develop new materials for learning those identified topics. The new materials refer to the usage of Computer Aided System (CAS) in specific Maple 9. We will build up graphical user interface (GUI) that provides two ways communication environment where input from user is required. These materials are dedicated to students whom will sit for MTH3004 in future with hope that they will have better ideas and understands these topics in much easier way in order to excel in MTH3004.